The Effect Of Intensification of Rainfed Paddy Rice on the Production of Rainfed Paddy Rice in Martapura Sub-District, East OKU Regency - Novalina; Rini Efrianti; Yunita Sari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study aims to analyze the effect of the intensification of rainfed lowland rice on rainfed lowland rice production in Martapura Sub-District, East OKU Regency. The type of research used in this study is a quantitative descriptive method. The data analysis used in this study is multiple regression analysis. The results showed that the rainfed lowland rice intensification program in Martapura Sub-District, East Ogan Komering Ulu Regency affected lowland rice production both partially and simultaneously. Variables use of high-yielding seeds (X1), use of dolomite (X2), use of urea fertilizer (X3), use of NPK fertilizer (X4), use of liquid organic fertilizer (X5), use of pesticides (X6) and labor (X7) have a positive effect and significant effect on lowland rice production in Martapura District, East Ogan Komering Ulu Regency. The variable that has the most influence on lowland rice production in Martapura Sub-District, East Ogan Komering Ulu Regency, is the use of superior seeds with a standard value of the partial regression coefficient (beta coefficient) of 3.099.